2018
DOI: 10.25100/socolen.v42i2.6684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capsicum baccatum and C. frutescens against Atta cephalotes (Hymenoptera: Formicidae) and the symbiotic fungus Leucoagaricus gongylophorus

Abstract: Leaf cutter ants are considered to be a major pest in the Neotropics, due to the considerable economic losses they cause by cutting large amounts of plant material to cultivate their symbiotic fungus. Their control is mainly achieved through synthetic products with adverse consequences to the environment and human health. In search for alternatives, the ethanolic extracts of leaves of Capsicum baccatum and C. frutescens (Solanaceae), were evaluated against medium size leaf cutter ant Atta cephalotes, and its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…The search for plant extracts or plant essential oils with insect repellent activity is a common research topic aimed at developing alternatives to synthetic chemicals for pest control (Lobo-Echeverri et al, 2016;Kim et al, 2017;Mangang et al, 2020;Nwanade et al, 2020;Rosa et al, 2020;Yarou et al, 2020). The repellent activity of these natural compounds has shown favorable results, as numerous studies have reported repellency and even death to insects after the application of plant-derived compounds (Ojo et al, 2020;Saraiva et al, 2020;Sharaby et al, 2020;Ya-Ali et al, 2020).…”
Section: Boletín Latinoamericano Y Delmentioning
confidence: 99%
“…The search for plant extracts or plant essential oils with insect repellent activity is a common research topic aimed at developing alternatives to synthetic chemicals for pest control (Lobo-Echeverri et al, 2016;Kim et al, 2017;Mangang et al, 2020;Nwanade et al, 2020;Rosa et al, 2020;Yarou et al, 2020). The repellent activity of these natural compounds has shown favorable results, as numerous studies have reported repellency and even death to insects after the application of plant-derived compounds (Ojo et al, 2020;Saraiva et al, 2020;Sharaby et al, 2020;Ya-Ali et al, 2020).…”
Section: Boletín Latinoamericano Y Delmentioning
confidence: 99%
“…Plant chemical defense strategies include the production of specific secondary/specialized metabolites (Fürstenberg-Hägg et al 2013). Several groups of secondary metabolites, such as alkaloids (Miyashira et al 2012), terpenes (Littledyke and Cherrett 1978;Pagnocca et al 1990;Verza et al 2011), andphenols (Nichols-Orians 1991) have been reported to be toxic for leaf-cutter ants (Cherrett 1972;Boulogne et al 2012;Van Bael et al 2011), or to inhibit the growth and development of their symbiotic fungus (Miyashira et al 2012;Lobo-Echeverri et al 2016). Indeed, the symbiont fungus of some Atta species have been reported to be able to detoxify certain phenolic compounds present in the leaves of foraged plants (Cherret 1980;Powell and Stradling 1986;Nichols-Orians 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Through co-evolutionary processes, many plants have evolved a plethora of secondary chemicals (e.g., flavonoids, sterols, coumarins, and sesquiterpene lactones) as defense mechanisms against the herbivore impact of leaf-cutter ants [5]. Some of these compounds exhibit antifungal activity against symbiotic fungi while others act as insecticides, and a few display bio-activity against both ants and symbiotic fungus [5].…”
Section: Introductionmentioning
confidence: 99%
“…Through co-evolutionary processes, many plants have evolved a plethora of secondary chemicals (e.g., flavonoids, sterols, coumarins, and sesquiterpene lactones) as defense mechanisms against the herbivore impact of leaf-cutter ants [5]. Some of these compounds exhibit antifungal activity against symbiotic fungi while others act as insecticides, and a few display bio-activity against both ants and symbiotic fungus [5]. In this way, although these secondary metabolites have no immediate or direct application in protecting the plants, an evaluation of their fractions against leaf-cutter ants may produce promising results for their use as control agents, and indicate the route to a commercially viable product.…”
Section: Introductionmentioning
confidence: 99%